“A Blurred Line”: The Role of District-Level Special Education Leaders in Interpreting Special Education Policy and Inclusion - Coviello, James; Mathieu-Sher, Reva (International Journal of Education Policy and Leadership)

(untitled) (Simon Fraser University, University of Delaware, Phi Delta Kappa International, 2025)
The U.S. law governing special education, the Individuals with Disabilities Act (IDEA), requires that students with disabilities be provided a free and appropriate public education (FAPE) in the least restrictive environment (LRE). However, given the interpretive latitude within the law and the wide discrepancy in how this law is applied, individuals making this determination within schools and district play a critical role in fostering inclusive educational systems for students with disabilities. This qualitative case study explores the role of local district-level special education leaders (DSELs) in interpreting LRE policy when attempting to create more inclusive environments. Findings reveal how LRE is implemented on the local level and highlight the unexplored role of DSELs. Implications for future research, policy, and practice are also discussed.